Gendered, Wired and Globalized - Gender and Globalization Issues in the New Information and Communication Technologies - Balleza, Mavic Cabrera (Review of Women's Studies; Vol 15 No 2 (2005): Review of Women's Studies Volume XV, Number 2 (July-December 2005))
Globalization is not an entirely new phenomenon. It is largely the same exploitative relationship between colonizers and their colonies. The new element in present-day globalization that makes it distinct from imperialism in the days of yore is the use of new information and communication technologies (ICTs). These new information and communication technologies have become the primary engine of growth for a globalized economy and have affected the way we live in an unprecedented manner. Women are one of the groups that have been hugely affected by ICT-powered globalization. The gender divide within the digital divide is one of the most significant forms of disparities that resulted from the digital revolution. However, there are also certain groups of women who have benefited from the opportunities that the new information and communication technologies offer. This paper examines the advantages that the new ICTs bring to women. It also analyzes the social, economic, political, and cultural challenges that women confront in an ICT-driven globalized world.